Effects of different biochars on antibiotic resistance genes during swine manure thermophilic composting - Wang, Jian; Sui, Bin; Shen, Yujun; Meng, Haibo; Zhao, Lixin; Zhou, Haibin; Li, Ran; Ding, Jingtao; Cheng, Hongsheng; Zhang, Xi (International Journal of Agricultural and Biological Engineering, 2018)
Elimination of antibiotic resistance genes (ARGs) in animal manure from concentrated animal feeding operations by thermophilic composting has drawn increasing attention. This study investigated the effects of sawdust biochar, corn stover biochar and peanut hull biochar with three spiked levels on ARGs in swine manure during thermophilic composting. Thirteen ARGs corresponding to four classes of antibiotics (tetracyclines, sulfonamides, macrolides and quinolones) were determined in the composting piles. Results indicated that the ten tested composting groups became fully mature after 30-day thermophilic composting process. tetM, tetO and ermB were reduced in all tested groups; tetC and tetG, tetX, sul1, sul2, ermF, qnrD and aac(6’)-Ib were mostly reduced under low level biochar addition but increased under higher level biochar addition; gyrA increased under medium biochar addition and reduced in other groups; oqxB remained comparatively stable throughout the composting process. The addition levels of spiked biochar are more important than types of spiked biochar on the removal of ARGs in the composting pile. The average removal rates of ARGs in the control group, low, medium and high level biochar addition groups were 0.24 logs, 0.52-0.72 logs, –0.52-0.18 logs and –0.19-0.21 logs, respectively. In summary, low level biochar addition could enhance the elimination of studied ARGs in swine manure during the composting process, while medium level biochar addition to the composting piles would increase the risk of ARGs’ propagation.Keywords: biochar, antibiotic resistance genes, thermophilic composting, swine manureDOI: 10.25165/j.ijabe.20181106.4667Citation: Wang J, Sui B, Shen Y J, Meng H B, Zhao L X, Zhou H B, et al. Effects of different biochars on antibiotic resistance genes during swine manure thermophilic composting. Int J Agric & Biol Eng, 2018; 11(6): 166–171.